Sore eyes as the most significant ocular symptom experienced by people with COVID-19: a comparison between pre-COVID-19 and during COVID-19 states. Issue 1 (30th November 2020) - Pardhan, Shahina; Vaughan, Megan; Zhang, Jufen; Smith, Lee; Chichger, Havovi
Abstract : Objective: Conjunctivitis has been reported in people suffering from COVID-19. However, many ocular symptoms are associated with the term 'conjunctivitis' which may be misleading. It is also unknown whether ocular symptoms were different in chronic sufferers of anterior eye diseases, when they were experienced or how long they lasted for compared with other COVID-19 symptoms. Methods: An online structured questionnaire obtained self-report data from people who had a confirmed diagnosis of COVID-19. Data for the type, frequency and duration of different COVID-19 symptoms were ascertained. Anterior eye symptoms experienced by participants in the pre-COVID-19 state were compared with during the COVID-19 state. Results: Data from 83 participants showed that the most reported COVID-19 symptoms were dry cough (66%), fever (76%), fatigue (90%) and loss of smell/taste (70%). The three most common ocular symptoms experienced by participants were photophobia (18%), sore eyes (16%) and itchy eyes (17%). The frequency of sore eyes was significantly higher (p = 0.002) during COVID-19 state (16%) compared with pre-COVID-19 state (5%). There were no differences between males and females (p>0.05). 81% of participants reported to have experienced ocular symptoms within 2 weeks of other COVID-19 symptoms, and 80% reported they lasted for less than 2 weeks. Conclusion: The most significant ocular symptom experienced by people suffering from COVID-19 was sore eyes. Other symptoms associated with other types of conjunctivitis, such as mucous discharge and gritty eyes linked to bacterial infection, did not reach significance. The term 'conjunctivitis' is too broad and should be used with caution.